2015
DOI: 10.1021/jz5027129
|View full text |Cite
|
Sign up to set email alerts
|

Contacts Between Alcohols in Water Are Random Rather than Hydrophobic

Abstract: Given the importance of water-mediated hydrophobic interactions in a wide range of biological and synthetic self-assembly processes, it is remarkable that both the sign and the magnitude of the hydrophobic interactions between simple amphiphiles, such as alcohols, remain unresolved. To address this question, we have performed Raman hydration-shell vibrational spectroscopy and polarization-resolved femtosecond infrared experiments, as well as random mixing and molecular dynamics simulations. Our results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
120
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(138 citation statements)
references
References 39 publications
18
120
0
Order By: Relevance
“…To address this, Raman-MCR and polarization-resolved femtosecond IR experiments were combined with random mixing and molecular dynamics simulations. (53) The conclusion of these studies was that from methanol to tertiary butyl alcohol there is no association driven by the HE.…”
Section: Positive Curvaturementioning
confidence: 92%
“…To address this, Raman-MCR and polarization-resolved femtosecond IR experiments were combined with random mixing and molecular dynamics simulations. (53) The conclusion of these studies was that from methanol to tertiary butyl alcohol there is no association driven by the HE.…”
Section: Positive Curvaturementioning
confidence: 92%
“…[36][37][38][39][40][41] Using Raman spectroscopy, Ben-Amotz et al have concluded that the observed clustering in alcohol-water mixtures is a result of random, rather than hydrophobic, interactions. 42,43 In contrast, some femtosecond midinfrared spectroscopy experiments have shown that water surrounding the aliphatic groups of the alcohols displays significantly slowed dynamics relative to the bulk, lending support to the model in which the measured negative excess entropy is attributed to water forming clathrate-like structure around the hydrophobic groups of the alcohols. 44 Here, we present a study of methanol-, ethanol-, and isopropanol-water mixtures via liquid microjet X-ray absorption spectroscopy (XAS).…”
Section: -17mentioning
confidence: 92%
“…The overall conclusion of their study indicates that the hydrophobic interactions between tert-butyl groups are responsible for selfaggregation of TBA molecules. 55 Very recently, Ben-Amotz 56 and Rankin 57 have shown that there are no more hydrophobic contacts in aqueous solutions of alcohols ranging from methanol to TBA than in random mixtures of the same concentration. Therefore, hydrophobic interactions between small hydrophobic groups are weaker than thermal energy fluctuations.…”
Section: Introductionmentioning
confidence: 99%